(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2023)
The article presents the e-commerce market and the payments made in this market. The purpose of the analysis is to examine the types of payments in the e-commerce market by individual customers (B2C). Research methods that have been used: analysis of literature in a given subject, diagnostic survey using the questionnaire technique, observation, comparative analysis.